Characterisation of intraocular lens injectors = Charakterisierung von Intraokularlinsen-Injektoren - Friedrich, Maximilian; Munro, Donald J.; Auffarth, Gerd U.; Khoramnia, Ramin (Klinische Monatsblätter für Augenheilkunde, 2024)
In modern ophthalmic surgery, an intraocular lens (IOL) is commonly implanted into the patientʼs eye with an IOL injector. Many injectors are available, showing various technological differences, from the early manually loaded injector systems to the modern preloaded injectors. This review aims to give a concise overview of the defining characteristics of injector models and draws attention to complications that may occur during IOL implantation. One can differentiate injectors according to their preoperative preparation (manually loaded or preloaded), their implantation mechanism (push-type or screw-type or combined or automated), the size of the nozzle tip, the presence of an insertion depth control feature, and the injectorʼs reusability. Potential complications are IOL misconfigurations such as a haptic-optic adhesion, adherence of the IOL to the injector plunger, an overriding plunger, uncontrolled IOL rotation, a trapped trailing haptic, or damage to the IOL. Additionally, during IOL implantation, the nozzle can become damaged with scratches, extensions, cracks, or bursts to the tip. While these complications rarely produce long-term consequences, manufacturers should try to prevent them by further improving their devices. Similarly, surgeons should evaluate new injectors carefully to ensure the highest possible surgical safety.
Gesehen am 18.09.2024